2010
DOI: 10.1098/rspb.2010.1158
|View full text |Cite
|
Sign up to set email alerts
|

Regional species pools control community saturation in lake phytoplankton

Abstract: Recent research has highlighted that positive biodiversity -ecosystem functioning relationships hold for all groups of organisms, including microbes. Yet, we still lack understanding regarding the drivers of microbial diversity, in particular, whether diversity of microbial communities is a matter of local factors, or whether metacommunities are of similar importance to what is known from higher organisms. Here, we explore the driving forces behind spatial variability in lake phytoplankton diversity in Fennosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
65
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 46 publications
10
65
0
Order By: Relevance
“…Further to this, a significant positive correlation was also found between b-diversity and chlorophyll a concentration, that is, an estimator of the biomass of primary producers, further supporting that the positive b-diversity-productivity relationship was the most prevailing pattern in our study. An increase in b-diversity with increasing productivity is frequently observed in nature as well as in experiments (Chase and Leibold, 2002;Chalcraft et al, 2008;Ptacnik et al, 2010), and previous studies have also shown that regions or metacommunities with higher environmental variability have higher b-diversity (Verleyen et al, 2009) and lower degrees of regional invariance (Ö stman et al, 2010). Here, we show that similar patterns are found within a single bacterial metacommunity over time.…”
Section: Discussionmentioning
confidence: 99%
“…Further to this, a significant positive correlation was also found between b-diversity and chlorophyll a concentration, that is, an estimator of the biomass of primary producers, further supporting that the positive b-diversity-productivity relationship was the most prevailing pattern in our study. An increase in b-diversity with increasing productivity is frequently observed in nature as well as in experiments (Chase and Leibold, 2002;Chalcraft et al, 2008;Ptacnik et al, 2010), and previous studies have also shown that regions or metacommunities with higher environmental variability have higher b-diversity (Verleyen et al, 2009) and lower degrees of regional invariance (Ö stman et al, 2010). Here, we show that similar patterns are found within a single bacterial metacommunity over time.…”
Section: Discussionmentioning
confidence: 99%
“…This fact emphasises that the concept of super-species depends on species traits and stressor identity. 'Super-species' occur in several phytoplankton bio diversityecosystem functioning experiments, especially under highly con trolled culture conditions (Ptacnik et al 2010). Natural fluctuations in real ecosystems will potentially reduce the role of such species, as the increased potential niche space allows for a variety of successful trait combinations rather than only one.…”
Section: Discussionmentioning
confidence: 99%
“…However, the importance of species identity effects in biodiversity−production relationships is frequently found and often related to trait combinations (for a discussion see Hillebrand & Matthiessen 2009). The presence of such 'super-species' that show high performance for multiple situations is a frequent phenomenon in experiments with a small species pool and low complexity of physical or biological structure (Weis et al 2008, Ptacnik et al 2010.…”
Section: Final Biovolume and Temporal Variation In Biovolumementioning
confidence: 99%
“…In the phytoplankton data sets from Mälardalen and Götaland, LRsite decreased in an eastward direction. This finding coincides with an increase in genus richness of phytoplankton in an eastward direction from the Atlantic coast toward Sweden and Finland, which could be related to changes in average phosphorus concentrations over larger spatial scales (>100 km) (Ptacnik et al 2008(Ptacnik et al , 2010. Whether these 2 patterns are linked and caused by the same mechanisms should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 96%
“…Yet, regional processes may be important as well, as some studies show that microbial communities display patterns related to spatial differences (Crump et al 2007, Soininen et al 2007, 2011, Vyverman et al 2007 or landscape scale environmental properties (e.g. average phosphorus levels in a region; Ptacnik et al 2008Ptacnik et al , 2010 and that variation in dispersal rates may affect community composition (Lindström & Östman 2011). …”
Section: Introductionmentioning
confidence: 99%